Museum making : narratives, architectures, exhibitions - Macleod, Suzanne; Hourston Hanks, Laura; Hale, Jonathan (Abingdon, Oxon [England] ; New York, NY : Routledge, 2012)
Over recent decades, many museums, galleries and historic sites around the world have enjoyed an unprecedented level of large-scale investment in their capital infrastructure, in building refurbishments and new gallery displays. This period has also seen the creation of countless new purpose-built museums and galleries, suggesting a fundamental re-evaluation of the processes of designing and shaping of museums. Museum Making: Narratives, Architectures, Exhibitions examines this re-making by exploring the inherently spatial character of narrative in the museum and its potential to connect on the deepest levels with human perception and imagination. Through this uniting theme, the chapters explore the power of narratives as structured experiences unfolding in space and time as well as the use of theatre, film and other technologies of storytelling by contemporary museum makers to generate meaningful and, it is argued here, highly effective and affective museum spaces. Contributions by an internationally diverse group of museum and heritage professionals, exhibition designers, architects and artists with academics from a range of disciplines including museum studies, theatre studies, architecture, design and history cut across traditional boundaries including the historical and the contemporary and together explore the various roles and functions of narrative as a mechanism for the creation of engaging and meaningful interpretive environments.
Narrative and Space -- Narrative and Perception -- Narrative, Media, Mediation.
Includes bibliographical references (pages [298]-304) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Museum architecture; Communication in architecture; Electronic books